ԽՍՀՄ–ի փլուզումը, «թուրք միասնության» գաղափարը և Ղարաբաղյան հարցը (1990-95–ականների թուրքական հրապարակումների լուսաբանմամբ) - Հովհաննսիյան, Անուշ («Զանգակ - 97»)
The collapse of Soviel Empire, metamorphosed into a messy and often tragically bloody disorder with a number of ethnic conflicts, the rise of ethnonationalism in the ex-Soviet successor states have radically changed the power balance in the huge region. It is natural, that neighbouring countrics, especially Turkey, had to reconsider its foreign policy, trying to use the phenomenon of mass political disintegration that occurred in the former USSR, to respond to the nationalistic movements in the Turkish-speaking republics of ex-USSR, and using ethnic, linguistic or religion identities, tried to fill in political vacuum. In such an atmosphere the idea of so called "Turkish Unity" is again pulled out from the pack Turkish policy and became the subject of animated discussion in Turkish media's, on the pages of academic magazines and on political and public forums.
Keywords: Պատմություն